Characterization of Halorubrum sfaxense sp. nov., a New Halophilic Archaeon Isolated from the Solar Saltern of Sfax in Tunisia - Hana Trigui; Salma Masmoudi; Céline Brochier-Armanet; Sami Maalej; Sam Dukan (International Journal of Microbiology)
An extremely halophilic archaeon, strain ETD6, was isolated from a marine solar saltern in Sfax, Tunisia. Analysis of the 16S rRNA gene sequence showed that the isolate was phylogenetically related to species of the genus Halorubrum among the family Halobacteriaceae, with a close relationship to Hrr. xinjiangense (99.77% of identity). However, value for DNA-DNA hybridization between strain ETD6 and Hrr.xinjiangense were about 24.5%. The G+C content of the genomic DNA was 65.1 mol% (T(m)). Strain ETD6 grew in 15–35% (w/v) NaCl. The temperature and pH ranges for growth were 20–55°C and 6–9, respectively. Optimal growth occurred at 25% NaCl, 37°C, and pH 7.4. The results of the DNA hybridization against Hrr. xinjiangense and physiological and biochemical tests allowed genotypic and phenotypic differentiation of strain ETD6 from other Hrr. species. Therefore, strain ETD6 represents a novel species of the genus Halorubrum, for which the name Hrr. sfaxense sp. nov. is proposed. The Genbank EMBL-EBI accession number is GU724599.